EFEK LAMA BIOKONVERSI OLEH JAMUR TIRAM PUTIH (Pleurotus ostreatus) TERHADAP KOMPONEN SERAT SABUT KELAPA TUA (The effect of bioconversion by the white oyster mushroom (Pleurotus ostreatus) to the fibrous component of old coconut fiber) - Arnold E. Manu; Twen Dami Dato; Yexal Kapitan; Gustaf Oematan (JURNAL NUKLEUS PETERNAKAN, 2022)
The purpose of this study was to determine the effect of bioconversion by white oyster mushroom (Pleurotus ostreatus) on the components of old coconut coir fiber. complete (CRD) consisting of 3 treatments and 3 replications. The treatments that were tried were R1 = old coconut husk with an incubation period of 40 days, R2 = old coconut husk with an incubation period of 50 days, R3 = old coconut husk with an incubation period of 60 days. The variables studied were the content of ADF, NDF, lignin, cellulose, and hemicellulose. The results showed that the use of white oyster mushrooms on the components of old coco fiber had no significant effect (P>0.05) on the content of ADF, NDF, lignin, cellulose and hemicellulose. It was concluded that the content of NDF, ADF, lignin, cellulose and hemicellulose was not affected by the increase in incubation time.